Language games - Wasielewski, Audrey Lynn, author; Faris, Suzanne, advisor; Moseman, Eleanor, committee member; Bates, Haley, committee member; McKee, Patrick, committee member (Colorado State University. Libraries, 2013)
The complex nature of language has interested me as long as I can remember: how we experience it and how it affects our lives in both personal and public ways. This fascination was the spark for a thesis body of work that considers Ludwig Wittgenstein's "language game" in the context of contemporary discourse. In his publication Philosophical Investigations, he first coins the term, noting that it is "meant to bring into prominence the fact that the speaking of language is part of an activity, or of a form of life." This idea that we activate language as we speak it, is the cornerstone of my personal exploration of the written and spoken word as a medium and the foundation of this thesis body.
Keywords: contemporary art; political rhetoric; language games; deconstruction